Intra-articular dexmedetomidine with bupivacaine versus bupivacaine alone for postoperative analgesia after knee arthroscopy. (4th March 2018) - Mostafa, Shaimaa F; Eid, Gehan M; Abdullah, Mohammed A; Elkalla, Rehab S
Abstract : Background: Optimal relief of pain after knee arthroscopy is essential for early rehabilitation and mobilisation and to minimise postoperative morbidity. This study's aim was to assess dexmedetomidine as an additive to intra-articular (IA) bupivacaine in terms of analgesic duration and postoperative rescue analgesic consumption following arthroscopic knee surgery. Methods: A total of 70 patients, ASA physical status I and II, undergoing knee arthroscopy under general anaesthesia were enrolled in this double-blinded randomised controlled study, after Pan African Clinical Trial Registry (PACTR201507001048242) approval was obtained. Patients were randomly assigned into two groups; the bupivacaine group (B) received IA 19 ml bupivacaine 0.5% + 1 ml normal saline, bupivacaine dexmedetomidine group (BD) received IA injection of 19 ml bupivacaine 0.5% + dexmedetomidine 100 μg (1 ml). Postoperative visual analogue pain score (VAS), duration of analgesia and postoperative analgesic requirement were assessed. Results: VAS scores at rest and on mobilisation were significantly lower in the BD group at 4 h, 6 h and 8 h postoperatively in comparison with group B ( p < 0.05). VAS scores were comparable between studied groups during the first 2 h, and at 12 h and 24 h postoperatively. Duration of analgesia was significantly longer in group BD (458.9 ± 93.5 min) than in the B group (229.1 ± 83.7 min) ( p < 0.05). Postoperative analgesic consumption was lowered in the BD group compared with the B group ( p < 0.05). Conclusions: Adding dexmedetomidine to IA bupivacaine after knee arthroscopy prolongs analgesic duration and decreases postoperative analgesic requirement.